Pengaruh Penggunaan Campuran Minyak Sawit dan Olein Sawit terhadap Sifat Fisikokimia dan Sensori Selai Cokelat - Hasrul Abdi Hasibuan; Aga Prima Hardika; Wawan Hendrawan (Pusat Penelitian Kelapa Sawit, 2022)
Palm oil is a semi-solid vegetable oil that has the potential to be used as fat in the manufacture of chocolate spread. In addition, the liquid fraction of palm oil (such as super olein) can increase the spreadability of chocolate spread. This research was conducted to evaluated the physicochemical and sensory properties of chocolate spread using a mixture of palm oil and super olein at a ratio of 71.4: 28.6, 57.1: 42.9, 42.9: 57.1, and 28.6: 71.4. Formulation of chocolate spread made with 35% fat, 44.6% sugar, 10% cocoa powder, 10% milk powder, 0.32% lecithin, 0.03% salt, and 0.05% vanilla. Chocolate spread was characterized by particle size, fat content, melting point, fatty acid composition, triacylglycerol composition and solid fat content, and organoleptic tests. Particle size and fat content were not significantly different, while melting point, fatty acids composition, triacylglycerol composition, and solid fat content were significantly different in each formula. The organoleptic tests showed that the amount of 71.4% super olein was preferred by panelists. In this formula, chocolate spread had a particle size of 0.08 mm, fat content of 40.0%, melting point of 19.2°C, fatty acids composition (palmitic acid 38.3%, stearic acid 6.7%, oleic acid 42.2%, and linoleic acid 9.9%), triacylglycerol composition (POP 35.9%, PLP 10.0%, POS 7.7%, POO 25.2%, and PLO 7.3%), and solid fat content at temperatures 25°C and 30°C were 5.4% and 2.1%, respectively.